2005
DOI: 10.1080/10810730500263810
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Multiple Tailored Messages for Smoking Cessation Among Callers to the Cancer Information Service

Abstract: Self-help materials computer-tailored to the specific needs of smokers have shown promise as a high-reach, low-cost intervention for smoking cessation. Adding tailored cessation materials to telephone-based cessation counseling may be a way of generating greater efficacy in promoting and maintaining cessation. The objective of this study is to assess the efficacy of adding different types of behavioral smoking cessation materials to brief telephone-based cessation counseling.A total of 1,978 smokers calling th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 16 publications
1
49
0
Order By: Relevance
“…Overall, 30 studies 34,[36][37][38][39][40][42][43][44]46,48,49,53,[55][56][57][58]61,66,69,72,75,80,88,91,96,97,109,110 that randomised between 72 and 3627 participants and followed up between 3 and 30 months evaluated the effect of tailored printed materials. In the meta-analysis, computer-generated, tailored printed materials were effective in increasing smoking cessation compared with no intervention or generic self-help materials.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, 30 studies 34,[36][37][38][39][40][42][43][44]46,48,49,53,[55][56][57][58]61,66,69,72,75,80,88,91,96,97,109,110 that randomised between 72 and 3627 participants and followed up between 3 and 30 months evaluated the effect of tailored printed materials. In the meta-analysis, computer-generated, tailored printed materials were effective in increasing smoking cessation compared with no intervention or generic self-help materials.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Loss to follow-up ranged from as low as 11% at 6 months 44 to 56% at 12 months. 75 Six studies 39,43,49,55,57,115 reported significant difference between intervention groups at baseline.…”
Section: Interventions and Co-interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers can use computer algorithms, online coaching, and proactive e-mail prompts to tailor treatment, or users can self-tailor by the use of chat rooms and selective browsing. E-Health can be used as a stand-alone treatment or as a treatment adjunct (Strecher et al, 2005). Research is needed to identify the active ingredients of this modality, as well as the efficacy of such emerging platforms as text messaging, social networking, and Twitter (e.g., Riley et al, 2008).…”
Section: Novel Channels For Treatment Deliverymentioning
confidence: 99%